Visual rapid naming and phonological abilities: different subtypes in dyslexic children - Araújo, Susana (2014)
One implication of the double-deficit hypothesis for dyslexia is that there should be subtypes of dyslexic readers that exhibit rapid naming deficits with or without concomitant phonological processing problems. In the current study, we investigated the validity of this hypothesis for Portuguese orthography, which is more consistent than English orthography, by exploring different cognitive profiles in a sample of dyslexic children. In particular, we were interested in identifying readers characterized by a pure rapid automatized naming deficit. We also examined whether rapid naming and phonological awareness independently account for individual differences in reading performance. We characterized the performance of dyslexic readers and a control group of normal readers matched for age on reading, visual rapid naming and phonological processing tasks. Our results suggest that there is a subgroup of dyslexic readers with intact phonological processing capacity (in terms of both accuracy and speed measures) but poor rapid naming skills. We also provide evidence for an independent association between rapid naming and reading competence in the dyslexic sample, when the effect of phonological skills was controlled. Altogether, the results are more consistent with the view that rapid naming problems in dyslexia represent a second core deficit rather than an exclusive phonological explanation for the rapid naming deficits. Furthermore, additional non-phonological processes, which subserve rapid naming performance, contribute independently to reading development.